2002
DOI: 10.1136/emj.19.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress in consultants in accident and emergency medicine: a national survey of levels of stress at work

Abstract: Objective: To assess levels of occupational stress in UK accident and emergency (A&E) consultants. Method: Postal survey of complete enumeration of UK consultants. Main outcome measures: GHQ-12 and SCL-D, and respondents' reported perceptions of stressors. Results: Of 371 valid respondents (78%), 21 declined to participate. Of the remaining 350, 154 (44.4%) had GHQ-12 scores over the threshold for distress, which is much higher than found in other studies of doctors. Levels of depression as measured by the SCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
120
7
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 13 publications
11
120
7
7
Order By: Relevance
“…We suggest that longer working hours increases job strain among pediatricians in Japan according to the job demands-control model, and increases psychosomatic symptoms, possibly through an increase in job strain. The association between longer working hours and more psychosomatic symptoms may also be explained by greater work-home interference among subjects who worked longer hours, which is known to affect psychological distress 1,3,4,7,16,19,36) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that longer working hours increases job strain among pediatricians in Japan according to the job demands-control model, and increases psychosomatic symptoms, possibly through an increase in job strain. The association between longer working hours and more psychosomatic symptoms may also be explained by greater work-home interference among subjects who worked longer hours, which is known to affect psychological distress 1,3,4,7,16,19,36) .…”
Section: Discussionmentioning
confidence: 99%
“…These include working hours 5,15,16) , overtime 17) , frequency of on-call duties 18) and work-home interference 1,3,4,7,19) . A few studies reported that long working hours were not associated with perceived stress at work 20) or psychological morbidity [21][22][23] .…”
mentioning
confidence: 99%
“…As medicine continues to adapt to changes in health-care economics, technology, and expectations for service deliverables, the potential for occupational stress and fatigue steadily increases [4,5]. Due to its insidious nature, occupational stress and fatigue often go undetected until a catastrophic event takes place, mandating a thorough review of the underlying cause (i.e., root cause analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Some attention has been paid to the role of acute stressors such as violence, trauma, bereavement and post-traumatic stress [16,17]. The adverse health and occupational outcomes of exposure to chronic stress, such as psychological illness, burnout and early retirement, have also been examined [18,19].…”
Section: Introductionmentioning
confidence: 99%